Unique Presentation of Urachal Cyst Disease: Incidental Finding to Complicated Infection - Seong K. Lee; Chauniqua Kiffin; Rafael Sanchez; Eddy Carrillo; Andrew Rosenthal (Case Reports in Urology)
Urachal remnant disease is uncommon in adults and can present with symptoms ranging from drainage near the umbilicus to a severe abdominal infection. Most cases are referred for treatment once diagnosed either clinically or radiographically with ultrasound or computerized tomography. We present a unique case of an infected urachal cyst visualized on a series of CT scans in an adult patient with abdominal pain over a period of years.